Style komunikacji w związkach kohabitacyjnych = Communication styles in cohabitation relationships - Janicka, Iwona (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The objective of the research was to analyse communication styles in cohabitation relationships. The group of 120 heterosexual couples (240 people) living in an informal relationship was examined. The control group consisted of 140 marriages (280 people). In total 520 people aged 21-44 were examined.
Keywords: komunikacja; małżeństwo; kohabitacja; marriage; communication; cohabitation